Variation in truck driver cardiovascular risk: Insights from a Brazilian public health initiative - Schettini, B; Dyer, C; Jani, A (2018)
In 2006, Brazil's newly initiated national database for Road Traffic Accidents (RTAs) highlighted that 43% of fatal RTAs on federal highways involved a truck. Truck drivers have greater exposure to cardiovascular risk factors and studies have suggested a link between poor cardiovascular health and involvement in RTAs. In 2007, the Brazil Federal Highway Police and the Social Transport Service joined forces with other agencies to implement Health Operations on Highways, a nationwide campaign to detect health risk factors in truck drivers, provide them with information about health and traffic safety and to ultimately reduce the number of traffic accidents on highways. This study evaluates baseline data of 91 health operations conducted across Brazil in 2013, where 11,572 truck drivers were tested for different cardiovascular risk factors (body weight/fat, abdominal/cervical circumference, hypertension, hyperglycemia, hypertriglyceridemia and hypercholesterolemia). Our study demonstrates, for the first time, how data from the Health Operations on Highways initiative can be used to highlight geographical variation in the prevalence of cardiovascular risk factors in professional truck drivers across all Brazilian states and also highlights unwarranted variation in the prevalence of these risk factors in truck drivers relative to the general population. Insights from our study can be used to design and implement health and care initiatives to minimize cardiovascular risk among truck drivers in a targeted way. Furthermore, the results of this study have important policy implications for Brazil and any other country dealing with a high rate of RTAs involving truck drivers.